PENGUATAN BRANDING DAN MANAJEMEN KEUANGAN UNTUK KEMAJUAN TOKO ROTI MARAULENG - Az zakiyyah, Nurul Azizah; Amalia Lubis, Firsty Ramadhona; Sukarniati, Lestari; Basia, Lusmino; Gatari , Altis Puspa; Apriliana, Dwi; Cholida, Maya Nur; Qurrota A’yun, Indanazulfa (INCIDENTAL : Journal Of Community Service and Empowerment, 2024)
This community service program aims to improve the branding and financial management of Toko Roti Marauleng, a micro-business in Yogyakarta. The program was carried out through two training sessions focusing on understanding product branding and structured financial record-keeping. The training included both theoretical and practical components, such as creating branding materials (stickers), managing social media, and using Excel for financial recording. The results demonstrated that Toko Roti Marauleng successfully improved its branding strategies through optimized social media use and more attractive packaging designs. Additionally, structured financial record-keeping was initiated, enabling the business to separate personal and business finances. These changes are expected to enhance the business's competitiveness, operational efficiency, and long-term sustainability.